121. A Respiratory Syncytial Virus Prefusion F Protein (RSVPreF3) Candidate Vaccine Administered in Older Adults in a Phase I/II Randomized Clinical Trial Is Immunogenic. (31st December 2020) - Guiñazú, Javier Ruiz; Tica, Jelena; Andrews, Charles P; Davis, Matthew G; De Smedt, Philippe; Essink, Brandon; Fogarty, Charles; Kerwin, Edward; Leroux-Roels, Isabel; Vandermeulen, Corinne; David, Marie-Pierre; Dezutter, Nancy; et al.
Abstract: Background: RSV causes significant disease burden in older adults, since reinfections are common and may lead to severe disease presentations while only supportive treatment is available. We present immunogenicity of different formulations of an investigational vaccine (RSVPreF3) in young and older adults. Methods: This is a phase I/II, placebo-controlled, multi-country trial (NCT03814590). Healthy adults aged 18–40 years were randomized 1:1:1:1 to receive 2 doses of either Low-, Medium- or High-dose of RSVPreF3 non-adjuvanted vaccine or placebo, 2 months apart. Following favorable safety outcomes, adults aged 60–80 years were randomized 1:1:1:1:1:1:1:1:1:1 in a 2-step staggered manner to receive 1 of the 9 RSV vaccine formulations containing Low-, Medium- or High-dose of RSVPreF3, non-adjuvanted or adjuvanted with AS01E or AS01B, or placebo (same schedule). Humoral and cellular-mediated immune responses are assessed before and after each dose; results up to 1 month post-dose 1 are shown here. Results: Of 48 adults aged 18–40 years and 1005 aged 60–80 years included in the exposed set, 42 and 933, respectively, were part of per-protocol set at 1 month post-dose 1. RSVPreF3 IgG geometric mean antibody concentrations were 8.4–13.5 and 7.2–12.8 fold-higher at 1 month post-dose 1 vs baseline in the 18–40- and 60–80-year-old vaccinees, respectively (Fig 1A). RSV-A neutralization activity significantly increased in all RSV vaccinees, geometric mean antibody titers being 7.5–13.7 and 5.6–9.9 fold-higher in 18–40- and 60–80-year-olds, respectively, at 1 month post-dose 1 vs baseline (Fig 1B). Geometric mean ratios of the fold increase between RSVPreF3 IgG antibody concentrations and RSV-A neutralizing antibody titers ranged between 0.9–1.1 in 18–40-year-old and 1.3–1.5 in 60–80-year-old vaccinees. A robust RSVPreF3-specific CD4+ T-cell response was elicited at 1 month post-dose 1 vs baseline in both 18–40- and 60–80-year-olds (Fig 2). Figure 1. RSVPreF3 IgG geometric mean antibody concentrations (GMCs, enzyme-linked immunosorbent assay, panel A), RSV-A neutralizing geometric mean antibody titers (GMTs, neutralization assay, panel B) Figure 2. RSVPreF3-specific CD4+ T-cells identified as expressing ≥2 markers among IL2, CD40L, TNF-□, IFN-□ (intracellular cytokine staining assay) Conclusion: One dose of RSVPreF3 candidate vaccine boosted humoral and cellular immune responses in all vaccinees. In older adults, higher humoral response, mostly neutralizing, was observed with increased RSVPreF3 antigen dosage and a tendency of higher cellular response was observed after adjuvanted formulations. Funding: GlaxoSmithKline Biologicals SA Disclosures: Javier Ruiz Guiñazú, MD MSc, GSK group of companies (Employee, Shareholder) Jelena Tica, PhD, GSK group of companies (Employee, Shareholder) Charles P. Andrews, MD, GSK group of companies (Scientific Research Study Investigator) Charles Fogarty, MD, GSK group of companies (Grant/Research Support) Edward Kerwin, MD, Amphastar (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)AstraZeneca (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Boehringer Ingelheim (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Chiesi (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Cipla (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)GSK group of companies (Employee, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Mylan (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Novartis (Employee, Advisor or Review Panel member, Research Grant or Support, Speaker's Bureau)other around 40 pharmaceutical companies (Other Financial or Material Support, conducted multicenter clinical research trials)Pearl (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Sunovion (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Theravance (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau) Isabel Leroux-Roels, MD PhD, GSK group of companies (Scientific Research Study Investigator) Corinne Vandermeulen, MD PhD, GSK group of companies (Other Financial or Material Support, My university only received Grant/Research Support) Marie-Pierre David, MSc, GSK group of companies (Employee, Shareholder) Nancy Dezutter, PhD, PharmD, RPh, GSK group of companies (Employee, Shareholder) Nathalie De Schrevel, PhD, GSK group of companies (Employee) Laurence Fissette, MSc, GSK group of companies (Employee) Narcisa Mesaros, MD, MSc, GSK group of companies (Employee)